Diminizing method of measure errors of phase radiation pattern microwave antennas - Mickhayluck, Y. P. (Видавництво Національного університету "Львівська політехніка", 2009)
At design of same types of microwave range antennas (for example, reflector) measuring of not only amplitude radiation pattern is required, but also phase radiation pattern. As a rule, there are not problems at measuring of phase radiation pattern antennas in low-frequency part of microwave range — measuring phase difference between supporting and measuring signals is carried out directly on RF. At measurings of phase radiation pattern antennas in high-frequency part of microwave range (centimetre and millimetric waves) signal frequency transformation is required downward on frequency (sometimes frequent), and then the phase difference of low intermediate frequency signals is measured. Errors show up thus, conditioned nonidentical phase-frequency and amplitudefrequency characteristics measuring device parallel channels. The offered method, based on parallel-cross commutation of signals in the measuring device channels, allows to remove these errors.
Keywords: phase radiation pattern; microwave antenna; measure error